2014
DOI: 10.1111/jdv.12833
|View full text |Cite
|
Sign up to set email alerts
|

A new vision of actinic keratosis beyond visible clinical lesions

Abstract: In actinic keratosis (AK), clinical and subclinical lesions coexist across large areas of sun-exposed skin resulting in field cancerization. The lesions are part of a disease continuum which can progress into invasive squamous cell carcinoma (SCC). Conventional biopsy sampling together with histopathological analysis of the excised tissue is still the gold standard for differentially diagnosing AK from invasive SCC and identifying the characteristic pathophysiological features of these lesions. Given that biop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
76
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(79 citation statements)
references
References 26 publications
1
76
0
1
Order By: Relevance
“…In the future, novel imaging techniques such as reflectance confocal microscopy and optical coherence tomography may be useful in the diagnosis of AK (5,26,27).…”
Section: Ak Diagnosismentioning
confidence: 99%
See 1 more Smart Citation
“…In the future, novel imaging techniques such as reflectance confocal microscopy and optical coherence tomography may be useful in the diagnosis of AK (5,26,27).…”
Section: Ak Diagnosismentioning
confidence: 99%
“…Treatment success parameters should ideally also take into consideration the ability of a therapy to eliminate subclinical lesions, though this depends on these lesions becoming detectable during treatment, or the use of specific imaging techniques for field cancerization (which are not usually available in dermatological offices) (26).…”
Section: J U S T a C C E P T E Dmentioning
confidence: 99%
“…Prevention of tumors before they become clinically manifested has always been the most affordable though not necessarily the most elusive way. SCC is considered to evolve from pre-cancerous entity - the actinic keratosis (AK) (31), a lesion previously been shown to be somewhat manageable by cryotherapy, curettage, electrosurgery and photodynamic therapy with 5-fluorouracil or topical imiquimod (32,33). It has been shown that if treat AK by these modalities early enough that the progression to SCC is highly unlikely.…”
Section: Introductionmentioning
confidence: 99%
“…3,5,6 Advanced imaging techniques show that areas of sun-exposed skin may contain both sub-clinical and clinically visible lesions, as well as areas of dysplastic cells in fields of cancerization. [6][7][8] Treating the entire field of sun-damaged skin, rather than only the clinically apparent lesions, is therefore ideal. Ingenol mebutate (IngMeb) (Picato ® LEO Pharma A/S Ballerup, Denmark) is indicated for the topical treatment of AK in areas of skin up to 25 cm 2 .…”
mentioning
confidence: 99%